Continuous Professional Development of Teachers Through Teaching Clinics at Muhammadiyah 28 Islamic Elementary School - Sintha Wahjusaputri; Suryadi Syarif; Sri Palupi Handayani; Ernawati Ernawati; Tashia Indah Nastiti (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
This study aims to develop the continuous professionalism of teachers through the Teaching Clinic at the Muhammadiyah 28 Islamic Elementary School, Jakarta. Continued professionalism requires high self-awareness of teachers to consistently build their profession regardless of educational qualifications, subjects, and levels of education. The research method uses Research Development with the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were teachers of grades I – VI of SD Islam Muhammadiyah 28 Jakarta. The results showed that teachers' need for continuous professional development was very high using a self-management model including self-mastery, self-motivation, self-management, material, and emotions. Further study has discovered that the resulting self-management model is feasible to use. This is shown by expert validation of 87% and practitioner validation of 83.5%. The study hopes to provide a self-management model for fostering continuous professionalism of teachers at SD Islam Muhammadiyah 28 Jakarta through the Teaching Clinic